Technological characterization and antibacterial activity of Lactococcus lactis subsp. cremoris strains for potential use as starter culture for cheddar cheese manufacture - CHENG,Tianfu (2022)
Abstract Several technological applications of Lactococcus lactis are attributed to their high metabolite-secreting abilities. Among these, bacteriocins can be used as food preservatives or additives in cheese manufacture. The objective was to evaluate the technological characteristics and antibacterial activity of 10 Lactococcus lactis isolates from traditional fermented dairy products, including acidifying ability, proteolytic ability, diacetyl production and autolytic activity. L. lactis subsp. cremoris Y14 and Y15 showed significantly (P < 0.05) higher ΔpH than other strains. L. lactis subsp. cremoris Y17 exhibited the highest proteolytic, L. lactis subsp. cremoris Y15 and L. lactis subsp. cremoris Y18 were next in terms of proteolytic activity. All strains possessed the ability of diacetyl production, with the highest production of 10.39 mg/g observed in L. lactis subsp. cremoris Y15. L. lactis subsp. cremoris Y14 had the highest (P < 0.05) autolytic ability (8.96%), followed by L. lactis subsp. cremoris Y15 (8.05%). L. lactis Y15 exhibited discernible antibacterial activity with the largest zone of inhibition diameters (25.56 mm). Based on the above results, L. lactis subsp. cremoris Y15 was selected as the starter to manufacture cheese. There were no significant differences in texture and sensory acceptability of Cheddar cheese manufactured by L. lactis subsp. cremoris Y15 with L. lactis subsp. lactis KLDS4.0325 or commercial starter. L. lactis subsp. cremoris Y15 can be used as a starter to produce Cheddar cheese.